Country Partnership Framework for Republic of Togo for the Period FY17-FY20 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
This country partnership framework (CPF), prepared jointly by the International Bank for Reconstruction and Development (IBRD), the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA) presents the World Bank Group’s (WBG’s) program for Togo during the period FY17 through FY20. The CPF is aligned with the Government of Togo’s forthcoming national development plan (PND) for 2018-2022, which focuses on forging a solid, stable democratic nation with strong, sustainable, inclusive growth; equitable access to good-quality social services; and respect for the environment. The overarching objective of the CPF is to help pave the way to more inclusive and sustainable growth in Togo, led both by a more dynamic private sector and more effective government policies, public investments, and services. The WBG’s strategy under the CPF emphasizes strengthening governance, including strengthening institutions and accountability, as a cross cutting theme integrated in three focus areas: (i) private sector performance and job creation; (ii) inclusive public service delivery; and (iii) environmental sustainability and resilience. The CPF seeks to take full advantage of the new International Development Association (IDA) 18 architecture and increased support for fragile states to scale up WBG support and promote joint IDA and IFC support. The CPF also seizes on a window of opportunity to support the government’s ambitious efforts to stabilize the macroeconomic framework and mitigate fiscal risks, a prerequisite for sustainable growth.